2017
DOI: 10.1523/jneurosci.3351-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Transforming Growth Factor Beta 1 Protects Synapses against Aβ Oligomers in Alzheimer's Disease Model

Abstract: Alzheimer's disease (AD) is characterized by progressive cognitive decline, increasingly attributed to neuronal dysfunction induced by amyloid-␤ oligomers (A␤Os). Although the impact of A␤Os on neurons has been extensively studied, only recently have the possible effects of A␤Os on astrocytes begun to be investigated. Given the key roles of astrocytes in synapse formation, plasticity, and function, we sought to investigate the impact of A␤Os on astrocytes, and to determine whether this impact is related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 81 publications
4
84
0
Order By: Relevance
“…, 2012 ), transforming growth factor beta 1 ( Diniz et al. , 2012 , 2014 , 2017 ), thrombospondin ( Christopherson et al. , 2005 ), and d -serine ( Henneberger et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2012 ), transforming growth factor beta 1 ( Diniz et al. , 2012 , 2014 , 2017 ), thrombospondin ( Christopherson et al. , 2005 ), and d -serine ( Henneberger et al.…”
Section: Discussionmentioning
confidence: 99%
“…When Aβ oligomers are injected into the hippocampus of mice, decrease in synaptic protein levels and atrophy of astrocytic processes occur. However, intracerbroventricular infusion of 10 ng TGF-β1 30 minutes before an injection of 10 pmol Aβ oligomers resulted in reduced levels of the proteins, drebrin, PSD-95, and synaptophysin, and strengthening of astrocytic processes [235] . Also, mice that were intracerebroventricularly injected with Aβ failed to spend more time with a novel object in a novel object recognition test, whereas the mice previously injected with TGF-β1 did not show memory impairments [235] .…”
Section: Additional Microglial Receptorsmentioning
confidence: 96%
“…Thus, release of these factors by microglia could be responsible for decreasing astrocytic synaptic engulfment. Other possible candidates for microglial-derived signals include TGFβ, which is known to reduce astrocytosis (Liddelow et al, 2017) and has also been shown to limit synapse loss following astrocyte activation (Diniz et al, 2017). Microglial derived FGF has been shown to be important for limiting astrocyte activation (Kang et al, 2014) although its specific effect on synaptic uptake by astrocytes…”
Section: Microglia Instruct Synaptic Elimination By Astrocytesmentioning
confidence: 99%